Social Factors of Stabilization of the Environmental Situation in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The population of the world, which is becoming increasingly globalized and developing at a rapid pace, is facing a great environmental threat today. Climate change, fresh water shortage, air pollution, accumulation of industrial and household waste, soil erosion, depletion of the ozone layer and other factors are examples of such problems. Therefore, the international community has already recognized its sanctity and inviolability and is fighting for its comprehensive protection. Environmental safety is one of the most important issues today and in the future. In the course of our article, together with the analysis of the social factors of the stabilization of the ecological situation in our country, we will consider the international experience, the formation of an ecological safety system based on modern science, the issue of ecological safety at the level of state policy, covering the territory of the country on a high scale, and the experience of leading countries.